ЛОГИКАТА, АРГУМЕНТАЦИЈАТА И ЈАЗИКОТ: ПОМЕЃУ АНАЛИТИКАТА И ДИЈАЛЕКТИКАТА (Филолошке студије, 2019)
In this paper an attempt is made to show that the new categories and conceptualisations that the argumentation theory, starting from the sixth decade of the twentieth century, has (re)introduced in the contemporary logical and lingusitc discourse, have arisen from its radical return to the ressources of the natural language in its argumentative and communicative function. In that way, the argumentation theory has largely contributed to the overcoming of the implicite reductionism of the axiomatic and formalistic approach, in favour of a larger conception of logic as a theory of rationality in all form of its manifestation, that is not only in its analytical, but also in its dialectical forms.